Unbroke [compact disc] - Evans, Sara, 1971- (Melody Place, 2024)
Multi-platinum country artist Sara Evans, known for chart-topping hits like Suds in the Bucket and A Little Bit Stronger, is poised for a new chapter. March 2024 marked her debut on Melody Place Records with the release of the single Pride and her long-awaited album. Simultaneously, she's preparing to unveil an updated version of her memoir, Born to Fly.